Adhesive sheet

The problem of increasing haze and insufficient light resistance of melanin is solved by using matrix polymers with low acid values ​​in the vinyl sheet and chromium or copper-based metal composite black dyes, and a vinyl sheet with low haze and high light resistance is achieved.

JP2025039054APending Publication Date: 2025-03-21NITTO DENKO CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023145816
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-08
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

Melanin in existing vinyl sheets increases the haze of the adhesive layer, affecting the design, light shielding and reflection properties, while the light resistance of melanin is insufficient.

Method used

Matrix polymer with an acid value of no more than 50 mgKOH/g and metal composite black dye are used. The metal composite dye is made of chromium or copper as a metal component and contains phthalene dye-based dye compound.

Benefits of technology

By using metal composite black dye soluble in adhesive components, the haze of the adhesive layer is reduced and the light resistance of the black adhesive layer is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025039054000001_ABST
    Figure 2025039054000001_ABST
Patent Text Reader

Abstract

To provide a black adhesive sheet that is suitable for ensuring superior black light resistance while suppressing haze.SOLUTION: An adhesive sheet 10 contains a base polymer and a metallic complex salt black dye. The base polymer has an acid value of 50 mgKOH / g or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a pressure-sensitive adhesive sheet. [Background technology]

[0002] In the manufacturing process of display panels such as organic EL panels, adhesive sheets are used as a bonding material between components. As such adhesive sheets, black adhesive sheets containing black pigments from the viewpoints of design, light blocking, or anti-reflection are known. Such adhesive sheets are described, for example, in the following Patent Document 1. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2013-32430 A Summary of the Invention [Problem to be solved by the invention]

[0004] The adhesive sheet described in Patent Document 1 contains a base polymer and a black pigment. Carbon black is preferably used as the black pigment. However, the black pigment disperses in the adhesive sheet without dissolving. Therefore, the black pigment increases the haze of the adhesive sheet. In order to ensure good design, light blocking properties, or anti-reflection properties in a black adhesive sheet, it is better for the haze to be low.

[0005] It is conceivable to use a black dye as the black component in the pressure-sensitive adhesive sheet, rather than using a black pigment as in Patent Document 1. However, black dyes have traditionally been associated with reduced black weather resistance.

[0006] The present invention provides a black-based pressure-sensitive adhesive sheet suitable for ensuring good black light resistance while suppressing haze. [Means for solving the problem]

[0007] The present invention [1] includes a pressure-sensitive adhesive sheet containing a base polymer having an acid value of 50 mgKOH / g or less and a metal complex black dye.

[0008] The present invention [2] includes the pressure-sensitive adhesive sheet according to the above [1], wherein the metal complex black dye contains at least one metal selected from the group consisting of chromium and copper.

[0009] The present invention [3] includes the pressure-sensitive adhesive sheet according to the above [1] or [2], in which the metal complex black dye contains an azo dye compound as a dye compound.

[0010] The present invention [4] includes the pressure-sensitive adhesive sheet according to the above [3], wherein the azo dye compound is an aromatic azo dye compound.

[0011] The present invention [5] includes the pressure-sensitive adhesive sheet according to any one of the above [1] to [4], wherein the metal complex black dye has a molecular weight of 400 or more.

[0012] The present invention [6] is * a * b * Transmittance hue in the color system b * The pressure-sensitive adhesive sheet according to any one of [1] to [5] above, wherein the value is 0 or less.

[0013] The present invention [7] includes the pressure-sensitive adhesive sheet according to any one of the above [1] to [6], which has a haze of 3.0% or less. Effect of the Invention

[0014] As described above, the pressure-sensitive adhesive sheet of the present invention contains a metal complex black dye as a black component. The dye can be dissolved in the pressure-sensitive adhesive composition forming the pressure-sensitive adhesive sheet during the manufacturing process of the pressure-sensitive adhesive sheet. Therefore, the dye can be dispersed well in the pressure-sensitive adhesive sheet compared to a pigment. Therefore, the pressure-sensitive adhesive sheet containing the dye as a black component is suitable for reducing the haze of the pressure-sensitive adhesive sheet.

[0015] In addition, in the pressure-sensitive adhesive sheet of the present invention, as described above, the acid value of the base polymer is 50 mgKOH / g or less. The pressure-sensitive adhesive sheet contains a base polymer with a low acid value of 50 mgKOH / g or less, which is suitable for ensuring the stability of the coordinate bond between the metal and the dye compound in the metal complex black dye (the higher the acid value of the base polymer, the more the coordinate bond is impaired). The stabilization of the metal complex black dye helps to ensure the light resistance of the metal complex black dye.

[0016] Therefore, the pressure-sensitive adhesive sheet of the present invention is suitable for ensuring good black light fastness while suppressing haze. [Brief description of the drawings]

[0017] [Figure 1] 1 is a schematic cross-sectional view of one embodiment of a pressure-sensitive adhesive sheet of the present invention. [Diagram 2] This shows an example of a method for producing an optical adhesive sheet shown in Fig. 1. Fig. 2A shows a step of forming a coating film of an adhesive composition, Fig. 2B shows a step of forming a base adhesive sheet, Fig. 2C shows a step of peeling one of the release liners, Fig. 2D shows a step of supplying a post-added component to the base adhesive sheet, and Fig. 2E shows a step of bonding the release liner to the adhesive sheet. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] As shown in Fig. 1, an adhesive sheet 10 according to one embodiment of the present invention has a sheet shape of a predetermined thickness and extends in a direction (plane direction) perpendicular to a thickness direction H. The adhesive sheet 10 has an adhesive surface 11 (first adhesive surface) and an adhesive surface 12 (second adhesive surface) opposite to the adhesive surface 11. Fig. 1 exemplarily shows a state in which release liners 21, 22 are attached to the adhesive surfaces 11, 12 of the adhesive sheet 10. The release liner 21 is in releasable contact with the adhesive surface 11. The release liner 22 is in releasable contact with the adhesive surface 12. The release liners 21, 22 are peeled off from the adhesive sheet 10 at respective predetermined times when the adhesive sheet 10 is used.

[0019] In this embodiment, the adhesive sheet 10 is a sheet-shaped pressure-sensitive adhesive formed from an adhesive composition. The adhesive composition contains a base polymer having an acid value of 50 mgKOH / g or less and a metal complex black dye. That is, the adhesive sheet 10 contains a base polymer having an acid value of 50 mgKOH / g or less and a metal complex black dye.

[0020] Examples of the base polymer include acrylic polymer, polyurethane polymer, polyamide polymer, and polyvinyl ether polymer. The base polymer may be used alone or in combination of two or more. From the viewpoint of ensuring good adhesion and transparency in the pressure-sensitive adhesive sheet 10, the base polymer is preferably an acrylic polymer.

[0021] An acrylic polymer is a copolymer of monomer components containing 50% by mass or more of (meth)acrylic acid ester. "(Meth)acrylic" means acrylic and / or methacrylic.

[0022] The (meth)acrylic acid ester is preferably an alkyl (meth)acrylate, and more preferably an alkyl (meth)acrylate having an alkyl group having 1 to 20 carbon atoms. Examples of such alkyl (meth)acrylate include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, s-butyl (meth)acrylate, t-butyl (meth)acrylate, pentyl (meth)acrylate, isopentyl (meth)acrylate, neopentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, and butyl (meth)acrylate. ) isooctyl acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, n-decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, n-tridecyl (meth)acrylate, isotridecyl (meth)acrylate, tetradecyl (meth)acrylate, isotetradecyl (meth)acrylate, pentadecyl (meth)acrylate, n-octadecyl (meth)acrylate, isooctadecyl (meth)acrylate, and nonadecyl (meth)acrylate. The (meth)acrylic acid alkyl ester may be used alone or in combination of two or more kinds. The (meth)acrylic acid alkyl ester is preferably at least one selected from the group consisting of methyl methacrylate (MMA), n-butyl acrylate (BA), and 2-ethylhexyl acrylate (2EHA).

[0023] The proportion of the (meth)acrylic acid alkyl ester in the monomer component is preferably 55 to 99.9% by mass, more preferably 60 to 99.5% by mass, and even more preferably 62 to 99% by mass. The proportion of the (meth)acrylic acid alkyl ester in the monomer component is preferably 55% by mass or more, more preferably 60% by mass or more, and even more preferably 62% by mass or more. When the proportion of the (meth)acrylic acid alkyl ester is equal to or more than the lower limit, the adhesive sheet 10 can appropriately exhibit basic properties such as adhesiveness. The proportion of the (meth)acrylic acid alkyl ester in the monomer component is, for example, 99.9% by mass or less, 99.5% by mass or less, or 99% by mass or less.

[0024] The monomer component may include a copolymerizable monomer that is copolymerizable with the (meth)acrylic acid alkyl ester. Examples of the copolymerizable monomer include a polar group-containing monomer. Examples of the polar group-containing monomer include a hydroxy group-containing monomer, a monomer having a nitrogen atom-containing ring, and a carboxy group-containing monomer. The copolymerizable monomer may be used alone or in combination of two or more kinds. The polar group-containing monomer is useful for modifying the acrylic polymer, such as ensuring the cohesive force of the acrylic polymer. The polar group-containing monomer is preferably at least one selected from the group consisting of a hydroxy group-containing monomer and a monomer having a nitrogen atom-containing ring.

[0025] Examples of the hydroxyl group-containing monomer include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, and 12-hydroxylauryl (meth)acrylate. The hydroxyl group-containing monomer is preferably at least one selected from the group consisting of 2-hydroxyethyl acrylate (2HEA), 4-hydroxyethyl acrylate (4HEA), and 4-hydroxybutyl acrylate (4HBA).

[0026] The ratio of the hydroxyl group-containing monomer in the monomer component is preferably 0.1 to 30% by mass, more preferably 0.5 to 20% by mass, and even more preferably 1 to 15% by mass. The ratio of the hydroxyl group-containing monomer in the monomer component is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, and even more preferably 1% by mass or more. When the ratio of the hydroxyl group-containing monomer is equal to or more than the lower limit, the cohesive force of the pressure-sensitive adhesive sheet 10 can be ensured, and the adhesive force of the pressure-sensitive adhesive sheet 10 to the adherend can be ensured. In addition, the ratio of the hydroxyl group-containing monomer in the monomer component is preferably 30% by mass or less, more preferably 20% by mass or less, and even more preferably 15% by mass or less. When the ratio of the hydroxyl group-containing monomer is equal to or less than the upper limit, the polarity of the acrylic polymer (related to the compatibility of the acrylic polymer with various additive components in the pressure-sensitive adhesive sheet 10) can be appropriately adjusted.

[0027] Examples of monomers having a nitrogen atom-containing ring include N-vinyl-2-pyrrolidone, N-methylvinylpyrrolidone, N-vinylpyridine, N-vinylpiperidone, N-vinylpyrimidine, N-vinylpiperazine, N-vinylpyrazine, N-vinylpyrrole, N-vinylimidazole, N-vinyloxazole, N-(meth)acryloyl-2-pyrrolidone, N-(meth)acryloylpiperidine, N-(meth)acryloylpyrrolidine, N-vinylmorpholine, N-vinyl-3-morpholinone, N-vinyl-2-caprolactam, N-vinyl-1,3-oxazin-2-one, N-vinyl-3,5-morpholinedione, N-vinylpyrazole, N-vinylisoxazole, N-vinylthiazole, N-vinylisothiazole, and acryloylmorpholine. The monomer having a nitrogen atom-containing ring is preferably N-vinyl-2-pyrrolidone (NVP).

[0028] The ratio of the monomer having a nitrogen atom-containing ring in the monomer component is preferably 1 to 30% by mass, more preferably 5 to 20% by mass, and even more preferably 8 to 17% by mass. The ratio of the monomer having a nitrogen atom-containing ring in the monomer component is preferably 1% by mass or more, more preferably 5% by mass or more, and even more preferably 8% by mass or more. When the ratio of the monomer having a nitrogen atom-containing ring is equal to or more than the above lower limit, the cohesive force of the pressure-sensitive adhesive sheet 10 can be ensured, and the adhesive force of the pressure-sensitive adhesive sheet 10 to the adherend can be ensured. In addition, the ratio of the monomer having a nitrogen atom-containing ring in the monomer component is preferably 30% by mass or less, more preferably 20% by mass or less, and even more preferably 17% by mass or less. When the ratio of the monomer having a nitrogen atom-containing ring is equal to or less than the above upper limit, the glass transition temperature of the acrylic polymer can be appropriately adjusted, and the polarity of the acrylic polymer (related to the compatibility of various additive components in the pressure-sensitive adhesive sheet with the acrylic polymer) can be appropriately adjusted.

[0029] Examples of carboxy group-containing monomers include acrylic acid, methacrylic acid, carboxyethyl acrylate, carboxypentyl acrylate, itaconic acid, maleic acid, fumaric acid, crotonic acid, and isocrotonic acid.

[0030] The ratio of the carboxyl group-containing monomer in the monomer component is preferably 0.0 to 3 mass%, more preferably 0.0 to 1 mass%, even more preferably 0.0 to 0.5 mass%, and even more preferably 0.0 to 0.1 mass%. The ratio of the carboxyl group-containing monomer in the monomer component is preferably 3 mass% or less, more preferably 1 mass% or less, even more preferably 0.5 mass% or less, even more preferably 0.1 mass% or less, and particularly preferably 0.0 mass%. When the ratio of the carboxyl group-containing monomer in the monomer component is the above upper limit or less, the acid value of the base polymer can be made 50 mgKOH / g or less. Furthermore, when the ratio of the carboxyl group-containing monomer in the monomer component is the above upper limit or less, corrosion by acid can be suppressed in the adherend of the pressure-sensitive adhesive sheet 10.

[0031] The monomer component may contain other copolymerizable monomers, such as acid anhydride monomers, sulfonic acid group-containing monomers, phosphoric acid group-containing monomers, epoxy group-containing monomers, cyano group-containing monomers, alkoxy group-containing monomers, and aromatic vinyl compounds.

[0032] The acrylic polymer can be formed by polymerizing the above-mentioned monomer components. Examples of the polymerization method include solution polymerization, emulsion polymerization, bulk polymerization, and photopolymerization. A polymerization initiator is used depending on the polymerization method. Examples of the polymerization initiator include a thermal polymerization initiator and a photopolymerization initiator. The amount of the polymerization initiator used is, for example, 0.05 parts by mass or more and, for example, 1 part by mass or less, relative to 100 parts by mass of the monomer components.

[0033] The thermal polymerization initiator may, for example, be an azo polymerization initiator or a peroxide polymerization initiator.The azo polymerization initiator may, for example, be 2,2'-azobisisobutyronitrile, 2,2'-azobis-2-methylbutyronitrile, or 2,2'-azobis(2-methylpropionate)dimethyl.The peroxide polymerization initiator may, for example, be dibenzoyl peroxide, t-butyl permaleate, or lauroyl peroxide.

[0034] Examples of the photopolymerization initiator include a radical photopolymerization initiator, a cationic photopolymerization initiator, and an anionic photopolymerization initiator. Examples of the radical photopolymerization initiator include an acylphosphine oxide photopolymerization initiator, a benzoin ether photopolymerization initiator, an acetophenone photopolymerization initiator, an α-ketol photopolymerization initiator, an aromatic sulfonyl chloride photopolymerization initiator, a photoactive oxime photopolymerization initiator, a benzoin photopolymerization initiator, a benzyl photopolymerization initiator, a benzophenone photopolymerization initiator, a ketal photopolymerization initiator, and a thioxanthone photopolymerization initiator.

[0035] From the viewpoint of ensuring the cohesive force of the adhesive sheet 10, the weight average molecular weight of the base polymer is preferably 100,000 to 5,000,000, more preferably 300,000 to 3,000,000, and even more preferably 500,000 to 2,000,000. The weight average molecular weight of the base polymer is preferably 100,000 or more, more preferably 300,000 or more, and even more preferably 500,000 or more. When the weight average molecular weight of the base polymer is equal to or more than the above lower limit, the cohesive force of the adhesive sheet 10 can be ensured. The weight average molecular weight of the base polymer is preferably 5,000,000 or less, more preferably 3,000,000 or less, and even more preferably 2,000,000 or less. When the weight average molecular weight of the base polymer is equal to or less than the above upper limit, the flexibility of the adhesive sheet 10 can be ensured. The weight average molecular weight of the acrylic polymer is measured by gel permeation chromatography (GPC) and calculated in terms of polystyrene.

[0036] The glass transition temperature (Tg) of the base polymer is preferably 0° C. or lower, more preferably −10° C. or lower, and even more preferably −20° C. or lower. The glass transition temperature is, for example, −80° C. or higher. That is, the glass transition temperature of the base polymer is preferably −80° C. to 0° C., more preferably −80° C. to −10° C., and even more preferably −80° C. to −20° C.

[0037] From the viewpoint of ensuring the cohesive force of the adhesive sheet 10, the base polymer preferably has a crosslinked structure. Examples of methods for introducing a crosslinked structure into the base polymer include the following first and second methods. In the first method, a base polymer having a functional group capable of reacting with a crosslinking agent and a crosslinking agent are blended into an adhesive composition, and the base polymer and the crosslinking agent are reacted in the adhesive sheet. In the second method, a polyfunctional compound (crosslinking agent) such as a polyfunctional monomer is included in the monomer components forming the base polymer, and a base polymer having a branched structure (crosslinked structure) introduced into the polymer chain is formed by polymerization of the monomer components. These methods may be used in combination.

[0038] The crosslinking agent used in the first method includes, for example, a compound that reacts with functional groups (such as hydroxyl and carboxyl groups) contained in the base polymer. Examples of such crosslinking agents include isocyanate crosslinking agents, epoxy crosslinking agents, oxazoline crosslinking agents, aziridine crosslinking agents, carbodiimide crosslinking agents, and metal chelate crosslinking agents, and preferably isocyanate crosslinking agents. The crosslinking agents may be used alone or in combination of two or more.

[0039] Examples of isocyanate crosslinking agents include tolylene diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, xylylene diisocyanate, hydrogenated xylylene diisocyanate, and diphenylmethane diisocyanate. In addition, examples of isocyanate crosslinking agents include derivatives of these isocyanates. Examples of the isocyanate derivatives include isocyanurate-modified products and polyol-modified products. Commercially available isocyanate crosslinking agents include, for example, Coronate L (a trimethylolpropane adduct of tolylene diisocyanate, manufactured by Tosoh), Coronate HL (a trimethylolpropane adduct of hexamethylene diisocyanate, manufactured by Tosoh), Coronate HX (an isocyanurate of hexamethylene diisocyanate, manufactured by Tosoh), and Takenate D110N (a trimethylolpropane adduct of xylylene diisocyanate, manufactured by Mitsui Chemicals).

[0040] The amount of the crosslinking agent in the first method is preferably 0.01 parts by mass or more, more preferably 0.05 parts by mass or more, and even more preferably 0.07 parts by mass or more, relative to 100 parts by mass of the base polymer, from the viewpoint of ensuring the cohesive strength of the adhesive sheet 10. From the viewpoint of ensuring good tackiness in the adhesive sheet 10, the amount of the crosslinking agent in the base polymer is preferably 10 parts by mass or less, more preferably 5 parts by mass or less, and even more preferably 3 parts by mass or less. From the viewpoint of achieving both the cohesive strength and good tackiness of the adhesive sheet 10, the amount of the crosslinking agent in the base polymer is preferably 0.01 to 10 parts by mass, more preferably 0.05 to 5 parts by mass, and even more preferably 0.07 to 3 parts by mass.

[0041] In the second method, the monofunctional monomer and the polyfunctional compound (crosslinking agent) may be polymerized in one step or in multiple steps. In the multistep polymerization method, the monofunctional monomer is first polymerized (preliminary polymerization), thereby preparing a prepolymer composition containing a partial polymer (a mixture of a polymer with a low degree of polymerization and an unreacted monomer). Next, the polyfunctional compound (crosslinking agent) is added to the prepolymer composition, and then the partial polymer and the polyfunctional compound are polymerized (main polymerization).

[0042] Examples of the polyfunctional compound include polyfunctional monomers and polyfunctional oligomers that contain two or more ethylenically unsaturated double bonds in one molecule. Examples of the polyfunctional monomer include polyfunctional (meth)acrylates.

[0043] Examples of the polyfunctional (meth)acrylate include difunctional (meth)acrylate, trifunctional (meth)acrylate, and tetrafunctional or higher polyfunctional (meth)acrylate.

[0044] Examples of bifunctional (meth)acrylates include ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, glycerin di(meth)acrylate, ethoxylated bisphenol A diacrylate (BPAEODE), and neopentyl glycol di(meth)acrylate.

[0045] Examples of trifunctional (meth)acrylates include trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, and tris(acryloyloxyethyl)isocyanurate.

[0046] Examples of tetrafunctional or higher polyfunctional (meth)acrylates include ditrimethylolpropane tetra(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol monohydroxypenta(meth)acrylate, alkyl-modified dipentaerythritol penta(meth)acrylate, and dipentaerythritol hexa(meth)acrylate.

[0047] Examples of polyfunctional oligomers include urethane (meth)acrylate oligomers, polyester (meth)acrylate oligomers, polyether (meth)acrylate oligomers, polyol (meth)acrylate oligomers, epoxy (meth)acrylate oligomers, polyethylene glycol di(meth)acrylate, and polypropylene glycol di(meth)acrylate.

[0048] The polyfunctional compound as the crosslinking agent in the second method may be used alone or in combination of two or more kinds. As the polyfunctional compound, at least one selected from the group consisting of 1,6-hexanediol diacrylate (HDDA) and dipentaerythritol hexaacrylate (DPHA) is preferably used.

[0049] The content of the base polymer in the pressure-sensitive adhesive sheet 10 is preferably 80 to 99.9% by mass, more preferably 90 to 99.5% by mass, and even more preferably 95 to 99.0% by mass. The content of the base polymer in the pressure-sensitive adhesive sheet 10 is preferably 80% by mass or more, more preferably 90% by mass or more, and even more preferably 95% by mass or more. When the content of the base polymer is equal to or more than the lower limit, the pressure-sensitive adhesive sheet 10 can appropriately exhibit basic properties such as adhesiveness. The content of the base polymer in the pressure-sensitive adhesive sheet 10 is preferably 99.9% by mass or less, more preferably 99.5% by mass or less, and even more preferably 99.0% by mass or less. When the content of the base polymer is equal to or less than the upper limit, the content of the metal complex black dye can be ensured.

[0050] From the viewpoint of the stability of the coordinate bond in the metal complex black dye, the acid value of the base polymer is preferably 30 mgKOH / g or less, more preferably 10 mgKOH / g or less, even more preferably 5.0 mgKOH / g or less, even more preferably 3.0 mgKOH / g or less, even more preferably 1.0 mgKOH / g or less, and particularly preferably 0.0 mgKOH / g. The acid value of the base polymer is, for example, 0.0 mgKOH / g or more. For example, the acid value of the base polymer can be adjusted by adjusting the composition (monomer composition) of the monomer components forming the base polymer. The adjustment of the monomer composition includes, for example, adjusting the ratio of the carboxyl group-containing monomer in the monomer components. The method of measuring the acid value of the base polymer complies with JISK0070:1992, and is specifically as described below with reference to the examples.

[0051] The metal complex black dye is a complex salt of a metal (central metal ion) and a dye compound (ligand). The metal complex black dye may be accompanied by a proton. The metal complex black dye can be used as a black component having a different color from carbon black (yellowish black). However, the black light resistance of an adhesive sheet containing a metal complex black dye varies depending on the acid value of the base polymer. The present inventors have obtained such knowledge. The present invention is based on such knowledge.

[0052] Examples of the metal (central metal ion) of the metal complex black dye include chromium, cobalt, nickel, and copper. From the viewpoint of the stability of the metal complex black dye, the metal of the metal complex black dye is preferably chromium or copper. That is, the metal complex black dye of the adhesive sheet 10 contains at least one metal selected from the group consisting of chromium and copper as the metal (central metal ion of the complex salt).

[0053] The dye compound (ligand) of the metal complex black dye is preferably an azo dye compound, more preferably an aromatic azo dye compound. The metal complex black dye may be a type in which the ratio (number ratio) of the dye compound to the metal is 1:1 (1:1 type complex salt), or a type in which the ratio (number ratio) of the dye compound to the metal is 2:1 (2:1 type complex salt). From the viewpoint of good color development in the adhesive sheet 10, the metal complex black dye is preferably a 2:1 type complex salt. The metal complex black dye as a 2:1 type complex salt formed from a metal M and an aromatic azo dye compound is shown below as structural formula (1).

[0054] [ka]

[0055] In structural formula (1), Ar 1 ~Ar 4 Each of Ar represents an aromatic ring which may have a substituent. Examples of the aromatic ring include a benzene ring, a naphthalene ring, an indene ring, and an anthracene ring. 1 ~Ar 4 The aromatic rings forming the formula (1) may all be the same, some may be the same, or all may be different. Examples of the substituent include a nitro group (-NO2), a sulfonic acid group (-SO3H), and a linear or branched alkyl group. Examples of the alkyl group include a methyl group, an ethyl group, a propyl group, an n-butyl group, an isobutyl group, an s-butyl group, a t-butyl group, an n-pentyl group, an isopentyl group, a neopentyl group, an n-hexyl group, an n-heptyl group, and a 2-ethylhexyl group. In addition, in the structural formula (1), X 1 ~X 4 Each represents -O- or -COO-. X 1 ~X 4 may be entirely the same or may be partially the same.

[0056] Examples of commercially available metal complex black dyes include Valifast Black 3804, 3807, 3808, 3810, 3820, 3830, 3840, 3866, 3870, 3877, and 3878 manufactured by Orient Chemical Industry Co., Ltd. Examples of commercially available metal complex black dyes include Orasol Black X45, X51, and X55 manufactured by BASF Japan Ltd. Examples of commercially available metal complex black dyes include Intraplast Black CN manufactured by Sensient Co., Ltd. Examples of commercially available metal complex black dyes include Aizenspiron Black BH and RLH manufactured by Hodogaya Chemical Co., Ltd.

[0057] The metal complex black dye may be used alone or in combination of two or more kinds.

[0058] The metal complex black dye has a bluish tinge in black color, and is therefore preferably at least one selected from the group consisting of the following structural formulas (2) to (4).

[0059] [ka]

[0060] [ka]

[0061] [ka]

[0062] The molecular weight of the metal complex black dye is preferably 400 or more, more preferably 500 or more, and even more preferably 600 or more, from the viewpoint of suppressing bleed-out from the pressure-sensitive adhesive sheet 10. The molecular weight of the metal complex black dye is preferably 50,000 or less, more preferably 40,000 or less, even more preferably 30,000 or less, and even more preferably 10,000 or less, from the viewpoint of ensuring compatibility with the base polymer. The molecular weight of the metal complex black dye is preferably 400 to 50,000, more preferably 500 to 40,000, even more preferably 600 to 30,000, and even more preferably 600 to 10,000, from the viewpoint of both suppressing bleed-out and ensuring compatibility. The molecular weight of the metal complex black dye is determined based on the structural formula of the metal complex black dye.

[0063] The content of the metal complex black dye in the adhesive sheet 10 is preferably 0.01% by mass or more, more preferably 0.05% by mass or more, and even more preferably 0.10% by mass or more, from the viewpoint of blackening the adhesive sheet 10. The content of the metal complex black dye in the adhesive sheet 10 is preferably 10% by mass or less, more preferably 7.0% by mass or less, and even more preferably 5.0% by mass or less, from the viewpoint of ensuring compatibility with the base polymer. The content of the metal complex black dye in the adhesive sheet 10 is preferably 0.01 to 10% by mass, more preferably 0.05 to 7.0% by mass, and even more preferably 0.10 to 5.0% by mass, from the viewpoint of achieving both blackening of the adhesive sheet 10 and ensuring the compatibility. In addition, the content of the metal complex black dye in the adhesive sheet 10 is preferably 0.01 parts by mass or more, more preferably 0.05 parts by mass or more, and even more preferably 0.10 parts by mass or more, relative to 100 parts by mass of the base polymer, from the viewpoint of blackening of the adhesive sheet 10. In order to ensure compatibility with the base polymer, the content of the metal complex black dye in the adhesive sheet 10 is preferably 10 parts by mass or less, more preferably 7.0 parts by mass or less, and even more preferably 5.0 parts by mass or less, per 100 parts by mass of the base polymer.

[0064] The pressure-sensitive adhesive composition may contain other components as necessary, such as a silane coupling agent, an ultraviolet absorber, a tackifier, a plasticizer, a softener, an antioxidant, a surfactant, and an antistatic agent.

[0065] Examples of the ultraviolet absorbent include a benzotriazole ultraviolet absorbent, a hydroxyphenyltriazine ultraviolet absorbent, a benzophenone ultraviolet absorbent, a salicylic acid ester ultraviolet absorbent, a cyanoacrylate ultraviolet absorbent, and a nickel complex salt ultraviolet absorbent. The ultraviolet absorbent may be used alone or in combination of two or more kinds.

[0066] Examples of the release liner 21 include a release liner having a release treatment layer on the surface of a liner substrate, and a release liner formed from a low-adhesion material. Examples of the liner substrate include a resin film and paper. Examples of the resin of the resin film include a polyester resin and a polycarbonate resin. Examples of the polyester resin include polyethylene terephthalate (PET) and polybutylene terephthalate. The release treatment layer can be formed by surface treating the liner substrate with a release treatment agent. Examples of the release treatment agent include a silicone release treatment agent, a long-chain alkyl release treatment agent, and a fluorine release treatment agent. Examples of the low-adhesion material include a polyolefin resin and a fluorine-based polymer. Examples of the polyolefin resin include polyethylene, polypropylene, and cycloolefin polymer (COP). Examples of the fluorine-based polymer include polytetrafluoroethylene.

[0067] Examples of the release liner 22 include a release liner having a release treatment layer on the surface of a liner substrate and a release liner formed from a low-adhesion material. Specifically, the release liner 22 is similar to that described above for the release liner 21.

[0068] The adhesive composition is prepared by blending a base polymer, a metal complex black dye, and other components added as necessary. The adhesive sheet 10 can be manufactured, for example, as follows using the adhesive composition (first manufacturing method). First, a solvent is blended into the adhesive composition to prepare a polymer solution (varnish). Examples of the solvent include ethyl acetate and toluene. Next, the polymer solution is applied onto a release liner 21 (first release liner) to form a coating film, and the coating film is dried and aged to form the adhesive sheet 10 from the coating film. Thereafter, if necessary, a release liner 22 is attached to the adhesive sheet 10 on the release liner 21. In the first manufacturing method, the metal complex black dye can be dissolved in a polymer solution containing a solvent. Therefore, the metal complex black dye can be dispersed well in the adhesive sheet 10 compared to a pigment (not soluble in a solvent).

[0069] The adhesive sheet 10 can also be produced, for example, by the following method (second production method).

[0070] First, a prepolymer composition is prepared. Specifically, a mixture (liquid) containing the monofunctional monomer for forming the base polymer and a photopolymerization initiator is prepared (prepolymer composition preparation step). Next, the mixture is irradiated with ultraviolet light to photopolymerize a portion of the monofunctional monomer in the mixture, thereby obtaining a prepolymer composition. Examples of light sources for ultraviolet light irradiation include ultraviolet LED lights, black light lamps, high-pressure mercury lamps, and metal halide lamps. In the ultraviolet light irradiation, the illuminance is, for example, 5 to 200 mW / cm. 2 m, and the cumulative irradiation dose is, for example, 100 to 5000 mJ / cm 2 The ultraviolet irradiation is preferably continued until the viscosity of the composition reaches about 15 to 25 Pa·s. This viscosity is measured using a Brookfield viscometer with a No. 5 rotor at a rotor speed of 10 rpm and at a temperature of 30°C. The prepolymer composition contains a photopolymerized product of a monofunctional monomer and a monofunctional monomer that has not undergone a polymerization reaction (residual monomer). The prepolymer composition does not contain a solvent.

[0071] Next, a multifunctional compound (crosslinking agent), an additional photopolymerization initiator, and other components as necessary are added to the prepolymer composition to prepare a pressure-sensitive adhesive composition (pressure-sensitive adhesive composition preparation step). Examples of other components include oligomers, antioxidants, silane coupling agents, and rust inhibitors. This pressure-sensitive adhesive composition does not contain a solvent. That is, the pressure-sensitive adhesive composition prepared in this step is a solvent-free pressure-sensitive adhesive composition.

[0072] Next, as shown in FIG. 2A, a coating film 10A is formed between release liners 21 and 22' (coating film forming step). Specifically, first, a pressure-sensitive adhesive composition is applied onto the release surface of release liner 21 to form coating film 10A. Examples of methods for applying the pressure-sensitive adhesive composition include roll coating, kiss roll coating, gravure coating, reverse coating, roll brushing, spray coating, dip roll coating, bar coating, knife coating, air knife coating, curtain coating, lip coating, and die coating. Next, the release surface of release liner 22' is bonded onto coating film 10A on release liner 21. For example, the same release liner as release liner 22 can be used as release liner 22.

[0073] Next, as shown in Fig. 2B, the coating film 10A between the release liners 21 and 22' is irradiated with ultraviolet light to form a base adhesive sheet 10B (base adhesive sheet forming step). When irradiated with ultraviolet light, a photopolymerization reaction proceeds in the coating film in a reaction system containing a monofunctional monomer (residual monomer) and a polyfunctional compound (crosslinking agent), forming a base polymer. Such a base polymer has a crosslinked structure in which linear units derived from the monofunctional monomer are linked by the polyfunctional compound.

[0074] Next, as shown in FIG. 2C, release liner 22' (FIG. 2B) is peeled off from base adhesive sheet 10B (peeling step).

[0075] Next, as shown in FIG. 2D, the later-added component is supplied to the base adhesive sheet 10B (later-added component supplying step). Specifically, a later-added component solution (not shown) containing the later-added component and a solvent is applied to the exposed surface of the base adhesive sheet 10B. Examples of the solvent include ethyl acetate and toluene. The later-added component includes a metal complex black dye. The later-added component may contain other components. Examples of the other additives include an ultraviolet absorber and an antioxidant. In this step, for example, the later-added component is allowed to penetrate into the base adhesive sheet 10B from the surface of the base adhesive sheet 10B, and the solvent is evaporated by heating as necessary. The metal complex black dye can be dissolved in the later-added component solution containing a solvent. Therefore, in this step, the metal complex black dye in the later-added component solution can be well dispersed in the adhesive sheet 10 after penetrating into the base adhesive sheet 10B as a later-added component. In addition, before this step, the base polymer has already had a crosslinked structure to form the base adhesive sheet 10B. Therefore, the orange peel surface is unlikely to be formed on base adhesive sheet 10B (is not substantially formed) by evaporation of the solvent in this step.

[0076] Next, as shown in FIG. 2E, another release liner 22 is laminated to the pressure-sensitive adhesive sheet 10 (lamination step).

[0077] In this manner, adhesive sheet 10 whose adhesive surface is covered and protected by release liners 21, 22 can be manufactured.

[0078] The adhesive sheet 10 can also be produced by a manufacturing method similar to the above-mentioned second manufacturing method, except for the following (third manufacturing method). In the adhesive composition preparation step, a metal complex black dye is added to a solventless adhesive composition. In the step shown in FIG. 2B, an adhesive sheet 10 is formed from the adhesive composition (containing a base polymer and a metal complex black dye). The steps shown in FIGS. 2C to 2E are not performed. This third manufacturing method can also produce an adhesive sheet 10 whose adhesive surface is covered and protected by release liners 21, 22.

[0079] In the second and third manufacturing methods, the pressure-sensitive adhesive sheet 10 can be produced from a solvent-free pressure-sensitive adhesive composition. Such a pressure-sensitive adhesive sheet 10 is suitable for reducing the environmental load. In other words, the pressure-sensitive adhesive sheet 10 formed from a solvent-free pressure-sensitive adhesive composition is environmentally friendly and preferable from the viewpoint of sustainable development.

[0080] The thickness of the pressure-sensitive adhesive sheet 10 is preferably 10 μm or more, more preferably 15 μm or more, and even more preferably 20 μm or more, from the viewpoint of ensuring sufficient adhesion to the adherend. The thickness of the pressure-sensitive adhesive sheet 10 is preferably 300 μm or less, more preferably 200 μm or less, even more preferably 100 μm or less, and even more preferably 50 μm or less, from the viewpoint of ease of handling and thinning of the pressure-sensitive adhesive sheet 10. The thickness of the pressure-sensitive adhesive sheet 10 is preferably 10 to 300 μm, more preferably 15 to 200 μm, even more preferably 20 to 100 μm, and even more preferably 20 to 50 μm, from the viewpoint of achieving both the above-mentioned adhesion and the above-mentioned ease of handling and thinning.

[0081] Adhesive sheet 10, L * a * b * Transmittance hue in the color system b * From the viewpoint of ensuring the blue tinge in the black color of the pressure-sensitive adhesive sheet 10, the value is preferably 0 or less, more preferably -1 or less, and even more preferably -2 or less.

[0082] From the viewpoint of ensuring the transparency required for the adhesive sheet 10 for use in a display panel, the haze of the adhesive sheet 10 is preferably 3.0% or less, more preferably 1.0% or less, and even more preferably 0.8% or less. The haze of the adhesive sheet 10 is, for example, 0.0% or more, 0.2% or more, or 0.4% or more. The method for measuring the haze is as described below in the examples.

[0083] As described above, the adhesive sheet 10 contains a metal complex black dye as a black component. The dye can be dissolved in a solution for forming the adhesive sheet 10 during the manufacturing process of the adhesive sheet 10. Therefore, the dye can be dispersed more favorably in the adhesive sheet 10 than a pigment. Therefore, the adhesive sheet 10 containing a dye as a black component is suitable for reducing the haze of the adhesive sheet 10.

[0084] As described above, the adhesive sheet 10 has a base polymer with an acid value of 50 mgKOH / g or less. The acid value is the amount (mg) of potassium hydroxide required to neutralize the acidic components contained in 1 g of the target. The smaller the acid value of the target, the fewer the acidic components there are in the target. The adhesive sheet 10 contains a base polymer with a low acid value of 50 mgKOH / g or less, which is suitable for ensuring the stability of the coordinate bond between the metal and the dye compound in the metal complex black dye (the higher the acid value of the base polymer, the more the coordinate bond is impaired). Stabilizing the metal complex black dye helps to ensure the light resistance of the metal complex black dye.

[0085] Therefore, the pressure-sensitive adhesive sheet 10 is suitable for ensuring good black light fastness while suppressing haze.

[0086] The adhesive sheet 10 is, for example, an optical adhesive sheet arranged at a light passing portion of a display panel. Examples of the display panel include a liquid crystal display panel and an organic EL display panel. The display panel has a laminated structure including elements such as a pixel panel, a polarizing film, a touch panel, and a cover glass. The adhesive sheet 10 is used, for example, in the manufacturing process of the display panel to bond elements included in the laminated structure. EXAMPLES

[0087] The present invention will be specifically described below with reference to examples, but the present invention is not limited to these examples. The specific values ​​of the blending amounts (contents), physical property values, parameters, etc. described below can be replaced with the upper limits (values ​​defined as "equal to or less than") or lower limits (values ​​defined as "equal to or more than") of the blending amounts (contents), physical property values, parameters, etc. corresponding to those described in the above-mentioned "Form for carrying out the invention".

[0088] Preparation of Acrylic Polymer P1 In a reaction vessel equipped with a reflux condenser, a nitrogen inlet tube, a thermometer and a stirrer, a mixture containing 63 parts by mass of 2-ethylhexyl acrylate (2EHA), 9 parts by mass of methyl methacrylate (MMA), 13 parts by mass of 2-hydroxyethyl acrylate (2HEA), 15 parts by mass of N-vinyl-2-pyrrolidone (NVP), 0.2 parts by mass of 2,2'-azobisisobutyronitrile (AIBN) as a polymerization initiator, and 233 parts by mass of ethyl acetate as a solvent was stirred under a nitrogen atmosphere at 60°C for 7 hours (polymerization reaction). This resulted in the production of a polymer solution S1 containing an acrylic polymer P1.

[0089] Preparation of Acrylic Polymer P2 In a reaction vessel equipped with a reflux condenser, a nitrogen inlet tube, a thermometer, and a stirrer, a mixture containing 99 parts by mass of butyl acrylate (BA), 1 part by mass of 4-hydroxybutyl acrylate (4HBA), 0.2 parts by mass of AIBN as a polymerization initiator, and 155 parts by mass of ethyl acetate as a solvent was stirred under a nitrogen atmosphere at 60° C. for 7 hours (polymerization reaction). This produced a polymer solution S2 containing an acrylic polymer P2.

[0090] Preparation of Acrylic Polymer P3 In a reaction vessel equipped with a reflux condenser, a nitrogen inlet tube, a thermometer, and a stirrer, a mixture containing 90 parts by mass of BA, 10 parts by mass of 4HBA, 0.2 parts by mass of AIBN as a polymerization initiator, and 233 parts by mass of ethyl acetate as a solvent was stirred under a nitrogen atmosphere at 60° C. for 7 hours (polymerization reaction). This produced a polymer solution S3 containing an acrylic polymer P3.

[0091] Preparation of Acrylic Polymer P4 In a reaction vessel equipped with a reflux condenser, a nitrogen inlet tube, a thermometer, and a stirrer, a mixture containing 95 parts by mass of BA, 5 parts by mass of acrylic acid (AA), 0.2 parts by mass of AIBN as a polymerization initiator, and 233 parts by mass of ethyl acetate as a solvent was stirred under a nitrogen atmosphere at 60° C. for 7 hours (polymerization reaction). This produced a polymer solution S4 containing the acrylic polymer P4.

[0092] Example 1 Preparation of Pressure-Sensitive Adhesive Composition To the polymer solution S1, 0.25 parts by mass (solid content equivalent) of an isocyanate crosslinker (product name "Takenate D110N", manufactured by Mitsui Chemicals) and 0.16 parts by mass (solid content equivalent) of a first black dye (product name "Valifast Black 3810", 1% by mass ethyl acetate solution, manufactured by Orient Chemical Industry Co., Ltd.) as a black component were added and mixed per 100 parts by mass of the acrylic polymer P1 to prepare an adhesive composition. The first black dye contains a metal complex black dye represented by the above structural formula (2), a metal complex black dye represented by the above structural formula (3), and a metal complex black dye represented by the above structural formula (4).

[0093] <Preparation of Adhesive Sheet> First, a pressure-sensitive adhesive composition was applied to the release-treated surface of a 38 μm-thick first release liner (product name "MRF#38", polyester film, manufactured by Mitsubishi Chemical Corporation) with one side being release-treated, to form a coating film. Next, this coating film was dried by heating at 132°C for 3 minutes. As a result, a 25 μm-thick adhesive layer was formed on the first release liner. Next, the release-treated surface of a 38 μm-thick second release liner (product name "MRE#38", polyester film, manufactured by Mitsubishi Chemical Corporation) with one side being release-treated was attached to the adhesive layer on the first release liner. Thereafter, aging treatment was performed at 60°C for 24 hours to promote the crosslinking reaction in the adhesive layer. In this manner, a black adhesive sheet (25 μm thick) with a release liner was produced as the adhesive sheet of Example 1.

[0094] Example 2 An adhesive sheet with a release liner of Example 2 was produced in the same manner as the adhesive sheet of Example 1, except for the following: In preparing the adhesive composition, polymer solution S2 (containing acrylic polymer P2) was used in place of polymer solution S1.

[0095] Example 3 An adhesive sheet with a release liner of Example 3 was produced in the same manner as the adhesive sheet of Example 1, except for the following: In preparing the adhesive composition, polymer solution S3 (containing acrylic polymer P3) was used in place of polymer solution S1.

[0096] Example 4 An adhesive sheet with a release liner of Example 4 was prepared in the same manner as the adhesive sheet of Example 1, except for the following: In preparing the adhesive composition, 0.16 parts by mass (solid content equivalent) of a second black dye (product name "Valifast Black 3820", 1 mass % MEK solution, manufactured by Orient Chemical Co., Ltd.) was blended as the black component in place of the first black dye. The second black dye is a metal complex black dye represented by the above structural formula (2).

[0097] Example 5 An adhesive sheet with a release liner of Example 5 was produced in the same manner as the adhesive sheet of Example 1, except for the following: In preparing the adhesive composition, polymer solution S2 (containing acrylic polymer P2) was used instead of polymer solution S1, and 0.16 parts by mass (solid content equivalent) of a second black dye (Valifast Black 3820) was blended in place of the first black dye as the black component.

[0098] Example 6 An adhesive sheet with a release liner of Example 6 was produced in the same manner as the adhesive sheet of Example 1, except for the following: In preparing the adhesive composition, polymer solution S3 (containing acrylic polymer P3) was used instead of polymer solution S1, and 0.16 parts by mass (solid content equivalent) of a second black dye (Valifast Black 3820) was blended in place of the first black dye as the black component.

[0099] Comparative Example 1 First, 0.25 parts by mass (solid content equivalent) of an epoxy crosslinker (trade name "Tetrad-c", manufactured by Mitsui Chemicals) and 0.16 parts by mass (solid content equivalent) of a first black dye (Valifast Black 3810) as a black component were added to and mixed with the polymer solution S4 per 100 parts by mass of the acrylic polymer P4 to prepare an adhesive composition. Thereafter, in the same manner as described above with respect to Example 1, a coating film of the adhesive composition was formed on the first release liner, the coating film was dried to form an adhesive layer, a second release liner (MRE#38) was attached to the adhesive layer, and the adhesive layer was subjected to an aging treatment. In this manner, a black adhesive sheet (thickness 25 μm) with a release liner was produced as the adhesive sheet of Comparative Example 1.

[0100] Comparative Example 2 An adhesive sheet with a release liner of Comparative Example 2 was prepared in the same manner as the adhesive sheet of Comparative Example 1, except for the following: In preparing the adhesive composition, 0.16 parts by mass (solid content equivalent) of a second black dye (Valifast Black 3820) was blended as the black component in place of the first black dye.

[0101] Comparative Example 3 An adhesive sheet with a release liner of Comparative Example 3 was prepared in the same manner as the adhesive sheet of Example 1, except for the following: In preparing the adhesive composition, 0.16 parts by mass (solid content equivalent) of a third black dye (product name: "OIL BLACK HBB", 1 mass% methyl ethyl ketone solution, manufactured by Orient Chemical Co., Ltd.) was blended as the black component in place of the first black dye. The third black dye is not a metal complex black dye.

[0102] Comparative Example 4 An adhesive sheet with a release liner of Comparative Example 4 was prepared in the same manner as the adhesive sheet of Example 1, except for the following: In preparing the adhesive composition, 0.16 parts by mass (solid content equivalent) of a fourth black dye (product name "Solvent Violet 13", 1 mass% methyl ethyl ketone solution, manufactured by Taiyo Fine Chemical Co., Ltd.) was blended as the black component in place of the first black dye. The fourth black dye is not a metal complex black dye.

[0103] Comparative Example 5 An adhesive sheet with a release liner of Comparative Example 5 was produced in the same manner as the adhesive sheet of Example 1, except for the following: In preparing the adhesive composition, a carbon black (CB) pigment (product name "ATDN101 Black", manufactured by Dainichiseika Color & Chemicals Mfg. Co., Ltd.) was blended as the black component in place of the first black dye at a ratio of 0.25% by mass in the adhesive layer.

[0104] <Haze, luminous transmittance, hue> For each of the pressure-sensitive adhesive sheets of the Examples and Comparative Examples, the haze, luminous transmittance (Y value), and hue were examined as follows.

[0105] First, a measurement sample was prepared. Specifically, after peeling off the second release liner from the adhesive sheet of the adhesive sheet with release liner (first release liner / adhesive sheet / second release liner), the adhesive sheet exposed by the peeling was attached to an alkali-free glass plate (thickness 0.55 mm, Eagle Glass, manufactured by Matsunami Glass Co., Ltd.). Next, after peeling off the first release liner from the adhesive sheet on the alkali-free glass, a polyethylene terephthalate (PET) film (product name "G981 E75", thickness 75 μm, manufactured by Mitsubishi Chemical Corporation) was attached to the adhesive sheet exposed by the peeling. This resulted in a laminate (alkali-free glass / adhesive sheet / PET film) containing the adhesive sheet. Next, the laminate was autoclaved under conditions of 50°C, 0.5 MPa, and 15 minutes. This resulted in a measurement sample.

[0106] The measurement samples were then measured using a spectrometer (HSP-150Vis, manufactured by Murakami Color Research Laboratory) to determine the haze, luminous transmittance, and hue. * value and b * The luminous transmittance was measured (first measurement). In this measurement, the measurement sample was placed in the device so that light was incident on the non-alkali glass side of the measurement sample. In this measurement, the measurement results (transmittance spectrum) obtained by measuring the laminate film of the above-mentioned non-alkali glass plate (Eagle Glass) and PET film (G981 E75) under the same conditions were used as a baseline. Specifically, the luminous transmittance is the transmittance (Y value) in the CIE-XYZ color system of light transmitted through the measurement sample at wavelengths of 380 nm to 780 nm. * value and b * The value is L for transmitted light. * a * b * Hue a in the color space * ,b * The measurement results are shown in Table 1. The luminous transmittance is shown in Table 1 as the Y value (%) before the light fastness test described later.

[0107] <Acid value of acrylic polymer> The acid value of each of the acrylic polymers P1 to P4 was measured in accordance with JIS K 0070:1992. Specifically, first, about 2 g of the acrylic polymer (sample) was precisely weighed out in a 100 mL container (Erlenmeyer flask) using a precision balance. Next, 10 mL of solvent was added to the container, and the acrylic polymer was dissolved in the solvent to prepare a first solution. As the solvent, a mixed solvent containing ethanol and diethyl ether in a mass ratio of 1:1 was used. Next, 1 to 3 drops of a phenolphthalein ethanol solution as an indicator were added to the first solution, and the solution was stirred. This resulted in a second solution (measurement solution). Then, the second solution was titrated with a 0.1 N potassium hydroxide-ethanol solution. In this titration, the end point of neutralization was determined to be when the color of the indicator (light red) continued for 30 seconds or more. Based on the results of the neutralization titration, the acid value of the acrylic polymer was calculated from the following formula. In the formula, B is the amount of 0.1N potassium hydroxide-ethanol solution used (mL), f is the factor of the 0.1N potassium hydroxide-ethanol solution, and 5.611 is the formula weight of potassium hydroxide, 56.11 × 10 -1 and S is the amount (g) of sample (acrylic polymer) collected.

[0108] Acid value (mgKOH / g)=(B×f×5.611) / S

[0109] <Light resistance test> A light resistance test was carried out on each of the pressure-sensitive adhesive sheets of the Examples and Comparative Examples as follows.

[0110] First, the measurement sample (alkali-free glass / adhesive sheet / PET film) used in the first measurement was placed in the chamber of a light resistance test device (product name "Super Xenon Weather Meter SX75", manufactured by Suga Test Instruments Co., Ltd.). Specifically, the test sample was placed in the chamber so that the PET film of the test sample was located on the light source (super xenon lamp) side. Next, in an environment of 55°C and relative humidity 55%, the adhesive sheet in the test sample was irradiated with light from a super xenon lamp (wavelength 300 nm to 400 nm) for 168 hours (light resistance test).

[0111] Then, the luminous transmittance of the measurement samples after the lightfastness test was measured using a spectrometer (product name "HSP-150Vis", manufactured by Murakami Color Research Laboratory Co., Ltd.) (second measurement). The method and conditions of this measurement were the same as those of the first measurement. The measured luminous transmittance is shown in Table 1 as the Y value (%) after the lightfastness test. The difference in Y value before and after the lightfastness test, ΔY value (Y value after test - Y value before test), is also shown in Table 1.

[0112] [evaluation] The adhesive sheet of Comparative Example 5 contained carbon black (CB) as the black component, and had a high haze of 4.5%. The adhesive sheets of Comparative Examples 3 and 4 contained a black dye compound (not a metal complex black dye) as the black component, and had a large ΔY value (Comparative Example 3: 16.7%, Comparative Example 4: 16.9%). The adhesive sheets of Comparative Examples 1 and 2 contained a metal complex black dye as the black component, but the acid value of the base polymer was more than 50 mgKOH / g, and the ΔY value was large (Comparative Example 1: 15.2%, Comparative Example 2: 14.4%). In other words, the adhesive sheets of Comparative Examples 1 to 4 had low black light resistance.

[0113] In contrast, each of the pressure-sensitive adhesive sheets of the Examples contained a metal complex black dye as a black component, and the acid value of the base polymer was 50 mgKOH / g or less. Each of the pressure-sensitive adhesive sheets of the Examples had a low haze of 1 or less. Furthermore, each of the pressure-sensitive adhesive sheets of the Examples had a small ΔY value of 6.5% or less (Example 5). In other words, the pressure-sensitive adhesive sheets of each Example had higher black light resistance than the pressure-sensitive adhesive sheets of Comparative Examples 1 to 4.

[0114] [Table 1] [Explanation of symbols]

[0115] 10 Adhesive sheet H Thickness direction 11 Page 1 12 Side 2 21,22 Release Liner

Claims

1. A base polymer having an acid value of 50 mg KOH / g or less; A pressure-sensitive adhesive sheet comprising a metal complex black dye.

2. The pressure-sensitive adhesive sheet according to claim 1 , wherein the metal complex black dye contains at least one metal selected from the group consisting of chromium and copper.

3. The pressure-sensitive adhesive sheet according to claim 1 , wherein the metal complex black dye contains an azo dye compound as a dye compound.

4. The pressure-sensitive adhesive sheet according to claim 3 , wherein the azo dye compound is an aromatic azo dye compound.

5. The pressure-sensitive adhesive sheet according to claim 1 , wherein the metal complex black dye has a molecular weight of 400 or more.

6. L * a * b * Transmittance hue in the color system b * The pressure-sensitive adhesive sheet according to claim 1 , wherein the value is 0 or less.

7. The pressure-sensitive adhesive sheet according to claim 1 , which has a haze of 3.0% or less.

Citation Information

Patent Citations

  • Black foil-like adhesive and black adhesive sheet

    JP2013032430A